PENGARUH STRUKTUR KEPEMILIKAN DAN MEKANISME CORPORATE GOVERNANCE TERHADAP BIAYA KEAGENAN (Studi Empiris Pada Perusahaan Keuangan Terdaftar di BEI Tahun 2008-2010) - Aga Nugroho Saputro; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2012)
This study examines the relationship between mechanism corporate governance, ownership structure and agency costs measured in term asset turn over and operating expense, general expense and administration expense. Collecting data using a purpose sampling method for financial companies listed in Indonesia Stock Exchange in 2008 until 2010. A total of 107 financial companies used a sample. The method of analysis of this study used multiple regression. The result of this study that the variable that affect agency costs is board compotiton, government ownership, institutional ownership, foreign ownership and concentrated ownership.